Investigation of hydrogen adsorption–absorption on iron by EIS - Amokrane, N.; Gabrielli, C.; Ostermann, E.; Perrot, H. (Electrochimica acta, 2007)
This work concerns the interaction between hydrogen and iron in the cathodic potential region. It was motivated by the need for a better understanding of the hydrogen insertion mechanism in metals. Electrochemical deposits of iron with various thicknesses were carried out on a gold substrate and they were characterized by impedance measurements under hydrogen evolution conditions. The processes occurring at the surface and within the iron films deposited on a gold electrode were studied using various electrochemical techniques. The impedance and voltammetric behaviours were strongly dependent on the film thickness. The main result of this study is that the charge transfer resistance increases with the film thickness. A model of the adsorption–absorption of hydrogen into iron films was proposed. It considered two types of absorbed hydrogen in a sublayer richer in hydrogen than the bulk metal. There, the hydrogen transported in the film coexists with another one coming from a direct absorption mechanism and “trapped” in some sites. The two absorbed hydrogen are reversibly exchanged. The interaction of hydrogen with palladium and iron was compared. It was concluded that for iron, the insertion of hydrogen results from a competition between a one-step direct hydrogen absorption mechanism and the classical two-step indirect penetration in the metal via the adsorbed hydrogen. At the end, a possible explanation of the deep penetration of the direct hydrogen absorption in the metal, detected by the impedance analysis, is proposed. It is based on the imperfections of numerous first layers of the deposited metals on polycrystalline gold.